O bóson de Higgs no modelo padrão das interações eletrofracas: aspectos fenomenológicos do setor escalar e resultados experimentais - Jeffery, Luciano [UNESP] (2015)
The objective of this work is to study the general aspects of the scale sector of the Standard Model the principle of gauge, which gives theoretical consistency to the electroweak model formulation, as well as spontaneous symmetry breaking and the Higgs mechanism, that are fundamental for the mass generation of the elementary particles, and gives rise to a new massive particle scale, the Higgs boson of whose value is not defined in the model. We present a study of the major modes of production and decay of Higgs boson as well as search of such particle in accelerators. We present a set of experimental results that have been published over the years in the major collaborations as LEP, Tevatron and LHC, which contributed in the long history of the Higgs boson search, until its identification in 2012